Factors Affecting Relapse of Tuberculosis - Muhammad Khurram, Ibrahim Mizhi Yong, Mian M Arshad, Hamama Tul Bushra Khar (Journal of Rawalpindi Medical College, 2009)
Background: To note factors affecting relapse of pulmonary tuberculosis (TB). Methods : This cross sectional, observational study was conducted in the department of Medicine, Rawalpindi Medical College and Allied Hospitals, from January 2004 to May 2006.Fifty patients suffering from relapse of pulmonary TB were included consecutively. Each patient underwent detailed clinical evaluation, and review of investigations to note factors affecting TB relapse. Age, gender, place of residence, overcrowding, educational status, occupation, monthly income, addiction/habits, history of contact with TB patients, body mass index (BMI), previous treatment related factors (radiological features, weight gain, directly observed short-course therapy [DOTS] implementation, and weight gain), and presence or absence of other diseases/conditions etc were noted. Factors present in ≥50% patients were considered important and then compared for statistical association with gender by Chi2 and T test wherever appropriate. P value <0.05 was considered significant. Results: Age <40 years (64%), male gender (62%), inner city over crowded residence (100%), illiteracy (62%), income <Rupees 5000/month (72%), contact with TB patient (64%), no weight gain(52%), failure of DOTS implementation (100%) during previous ATT course, and anemia (70%) were present in ≥50% patients. Significant gender based difference was notable in employment status and weight gain during previous ATT course only. Conclusion: Inner city, over crowded residence and lack of DOTS implementation are most frequently noted factors in TB relapse patients